IDENTIFIKASI PANAS BUMI DIWAK DAN DEREKAN KECAMATAN BERGAS KABUPATEN SEMARANG DENGAN MENGGUNAKAN METODE AUDIOMAGNETOTELLURIK - Elvera Yuanita Rukmana; Udi Harmoko (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Audio-Magnetotellurics (AMT) surveys has been conducted in September 2013 in the Diwak and Derekan geothermal fields. The purpose of the audio-magnetotelluric surveys to indicate heat source, reservoir, and cap rock. The data obtained from the field was apparent resistivity, phase difference, and coherence as a function of frequency are processed using softwere package WinGLink then matched with regional geological information studies, and the results are interpreted.Characterization of geothermal systems include the caprock with a resistivity of 0-10Ωm value where the area is a zone of conductivity. Then the reservoir area is suspected to have a resistivity value with arange of 50-500 Ωm with a depth of about 500 m. In the heat source located in a geothermal system resistivity values > 500Ωm with a depth of about 1.5 km. Keywords: AMT, geothermal, resistivity